STUDI HISTOLOGI DUODENUM CODOT (Rousettus sp.) DENGAN PEWARNAAN ALCIAN BLUE pH 2,5-PERIODIC ACID SCHIFF (AB pH 2,5-PAS) - , CLARA NOVITASARI; , drh. Ariana, M.Phill ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia has 205 species of bats that constitutes 21 % kind of the bats in the world. Bat is divided into 2 subordo which are Megachiroptera & Microchiroptera. Codot is the bats which included in the subordo of Megachiroptera, the bat which eat fruits and nectar. While subordo Microchiroptera is insectivorous bat. Research on the structure of duodenum codot (Rousettus sp.) histology become important because of those differences. Sample of this research was three dudenum codot that obtained from region of Bantul. These sample was fixation, dehidration, clearing, and embedding. Then followed by block cutting with 5-6 Î¼m thickness. Staining was done by using routine Hematoxylin-Eosin staining early confirmation of the histological structure and Alcian Blue pH 2.5âPeriodic Acid Schiff (AB pH 2.5- PAS) was used to determinethe distribution of mucopolysaccharides in the duodenum codot. Staining results analized with descriptive result analysis. The histological structure of the duodenum codot (Rousettus sp.) has similarity with such frugivore bats such Sturnira lilium and other mammals. Villi of duodenum codot is short and branched. Lamina muscularis mukosae codot is very thin because it is composed of only one layer of smooth muscle. Brunner glands in the codot tunica submucosa fills the anterior portion of the duodenum. Intestinum length has Brunner Glands is 4503.57 Â± 4329.88 Î¼m. Internus circular lamina muscularis and externus longitudinal lamina muscularis has same thickness as plexus myenterikus in between. Goblet cells in the epithelium and kripte Lieberkuhn were acid because stained strong blue or positively reacted to Alcian Blue staining while the columnar cell in the lamina epitelialis mukosae, the columnar cell Kripte Lieberkuhn, and the Brunner glands in the tunica submucosa were neutral because they were stained magenta or positively reacted to the Periodic Acid Schiff staining.